Variation in Nutritional Quality of By-Products from Nine Organic Apple Cultivars - Elisabeta Elena Popa; Laurentiu Mihai Palade; Violeta Alexandra Ion; Andreea Barbu; Oana Crina Bujor; Vlad Ioan Popa; Paul Alexandru Popescu; Amalia Carmen Mitelut; Mihaela Cristina Draghici; Mihaela Geicu-Cristea; Mona Elena Popa (Food Technology and Biotechnology)
Research background. Recently, consumers have been increasingly interested in highly nutritional and health-promoting products in the form of functional foods that are produced using environmentally friendly processes as part of the circular economy. Therefore, much research has been carried out related to the valorisation of waste generated during the processing of food, especially fruit and vegetables, commonly referred to as by-products. These by-products consist of peels, seeds, stems or pomace, which have been shown to have valuable nutritional properties (high content of polyphenols, vitamins, antioxidants, etc.). Experimental approach. Considering these aspects, the aim of this study is to characterise three types of by-products of apple processing, namely peel, pulp pomace and whole fruit pomace, from a nutritional point of view. The total content of polyphenols, antioxidant activity, ascorbic acid (vitamin C) and phenolic content were determined in nine apple varieties from two harvest years (2020 and 2021) during 9 months of storage. Results and conclusions. The results showed that apple peel had good nutritional properties, in contrast to the pulp or the whole fruit, which are often removed during apple processing. Therefore, the analysed by-products are suitable candidates for application in the food industry for the development of new products enriched with bioactive compounds. Novelty and scientific contribution. In this study, nine varieties of organic apples were analysed and the nutritional parameters were determined. The phenolic compounds of the studied apple by-products were analysed for possible reuse of apple processing waste.